2005
DOI: 10.1055/s-2005-837754
|View full text |Cite
|
Sign up to set email alerts
|

Four New 6-Nor-5(6→7)abeo-abietane Type Diterpenes and Antitumoral Cytotoxic Diterpene Constituents from the Bark ofTaiwania cryptomerioides

Abstract: Four new 6-nor-5(6-->7) abeo-abietane type diterpenes designated as taiwaniaquinone G, taiwaniaquinone H, taiwaniaquinol E and taiwaniaquinol F and eight known diterpenes, taiwaniaquinones A (5), D (6), E, F (8), and taiwaniaquinols A (9), B, C (11), D (12) were isolated from the bark of Taiwania cryptomerioides. Their structures were elucidated on the basis of spectroscopic studies. These twelve diterpenes were evaluated for in vitro antitumoral cytotoxic activity. The result demonstrated that compounds 5, 6,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
77
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 19 publications
2
77
0
Order By: Relevance
“…The taiwaniaquinoids are a family of unusual diterpenoids possessing a [6,5,6]- abeo -abietane skeleton that was unknown in nature prior to 1995 17. Each member of this family contains a benzylic quaternary stereogenic center (Figure 1).…”
mentioning
confidence: 99%
“…The taiwaniaquinoids are a family of unusual diterpenoids possessing a [6,5,6]- abeo -abietane skeleton that was unknown in nature prior to 1995 17. Each member of this family contains a benzylic quaternary stereogenic center (Figure 1).…”
mentioning
confidence: 99%
“…18) In these woods, a variety of biologically active abietane-type and two pimarane-type diterpenoids have been isolated. [22][23][24][25][26][27][28][29][30][31] These reports are indicative that yellow hornets utilize these woods not only for building material for the nest but also as a chemical tool to protect the nest from microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29][30][31] However, these molecular mechanisms have not been well examined. Ross reported that an anticancer quinone classified as an abietane terpenoid exhibited apoptosis, based on morphological changes in the cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our particular attention was taken by the norditerpene taiwaniaquinone G (6). [5] This molecule has not only undergone biosynthetic excision of a carbon atom, but it also lacks the unsaturation and/or oxygen functionality that would be immediately amenable to biomimetic chemistry. Taiwaniaquinone G (6) has been the target of two previous syntheses (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%